2018
DOI: 10.1177/1534735418807555
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerobic and Resistance Exercises on Physical Symptoms in Cancer Patients: A Meta-analysis

Abstract: Objective. This study aimed to conduct a meta-analysis to establish the effect of exercise interventions on physical symptoms, including fatigue, nausea/vomiting, pain, dyspnea, insomnia, loss of appetite, constipation, and diarrhea in cancer patients and survivors. Methods. We searched articles published before April 2017 using the following databases: Cochrane Library, PubMed/MEDLINE, CINAHL, Scopus, PEDro, Health & Medical Collection, and Psychology Database. Randomized controlled trials (RCTs) of exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 52 publications
1
64
3
3
Order By: Relevance
“…One may perceive that the intensity of exercise involved in the intervention could be a factor for the discrepancies observed, as evidenced by the difference in the effect of a home-based walking program and a program combining resistance and aerobic exercises on joint pain [35,38]. However, as reported in a recent meta-analysis, interventions involving different types of exercises were consistently shown to reduce pain, fatigue and insomnia among patients of various cancer types [54]. This finding prompts that intensity of exercise involved in an intervention is unlikely to have affected intervention effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…One may perceive that the intensity of exercise involved in the intervention could be a factor for the discrepancies observed, as evidenced by the difference in the effect of a home-based walking program and a program combining resistance and aerobic exercises on joint pain [35,38]. However, as reported in a recent meta-analysis, interventions involving different types of exercises were consistently shown to reduce pain, fatigue and insomnia among patients of various cancer types [54]. This finding prompts that intensity of exercise involved in an intervention is unlikely to have affected intervention effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Both pharmacological and non-pharmacological treatments and/or interventions have been shown to be effective for the components of the cluster. Pain can be treated using resistance exercise techniques and medications [43,44]. Mood disorders, including depression, can be treated using medication and a variety of psychotherapies, depending on the cause [45].…”
Section: Discussionmentioning
confidence: 99%
“…Frist, Nakano et al published the most recent meta-analysis limited to RCTs using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-C30 (EORTC-QLQ-C30) [39] (Table 1, Section 4. General exercise therapy).…”
Section: State-of-the-artmentioning
confidence: 99%
“…The meta-analysis showed that pain in the intervention group (receiving aerobic and/or resistance exercises) was significantly lower compared to no intervention. However, the effect size was only small (SMD of −0.17 (95%CI, −0.32 to 0.03)) and no differences among the 3 types of exercises interventions could be extracted [39]. Second, two Cochrane reviews of Mishra et al summarized the effectiveness of exercise interventions on health-related quality of life, including pain, during active cancer treatment [34] and in cancer survivors [33], respectively (Table 1, Section 4.…”
Section: State-of-the-artmentioning
confidence: 99%